Teaching of writing to 6° and 7° grade students - Barbagli, Alessia; Lucisano, Pietro; Sposetti, Patrizia (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2017)
This paper provides a reflection on strategies and actions used in teaching writing to lower secondary school students. Specifically, this contribution focuses on some of the results of a two-year research (2012/2014) based on the analysis of writing compositions by students of the first two years of secondary school. Datas concern a) the design and action of teaching by a group of mother tongue teachers from seven schools of Rome; b) the analysis of instructions for students’ written composition used in the two years from such teachers. The school has felt for long time the need to rethink its methods of teaching/learning the language and the four basic language skills, writing in particolar. In keeping with this need, the results highlight experimented educational projects in schools and attitudes of teachers, responding to the need for studies and contributions to the reflection on the issue in view of didactic effects.